2022
DOI: 10.1038/s41598-022-19524-7
|View full text |Cite
|
Sign up to set email alerts
|

The dual neural effects of oxytocin in autistic youth: results from a randomized trial

Abstract: Recent discoveries have highlighted the effects of oxytocin (OT) on social behavior and perception among autistic individuals. However, a gap persists in the literature regarding the potential effects of OT and the neural temporal dynamics due to OT administration. We explored the effect of OT on autistic individuals using magnetoencephalography (MEG), focusing on M100, M170, and M250, social perception-related components that tend to show atypical patterns in autistic individuals. Twenty-five autistic adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Gordon et al [ 1 ] found that the administration of OXT led to increased activity in brain regions crucial for processing social-emotional information and enhanced the connectivity between nodes of the brain’s reward and social-emotional processing systems specifically during social stimuli, including increased functional connectivity of the amygdala with the ventromedial PFC, the orbitofrontal cortex and the precuneus. Similarly, Korisky et al [ 73 ] found that OXT increased neural activity in the frontal regions of the brain in response to social stimuli, as well as in the left hemisphere regardless of the stimulus. Takiguchi et al [ 77 ] discovered that OXT administration enhanced activation in the right middle frontal gyrus and striatum, consistent with enhancements in the mesolimbic dopaminergic reward system.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Gordon et al [ 1 ] found that the administration of OXT led to increased activity in brain regions crucial for processing social-emotional information and enhanced the connectivity between nodes of the brain’s reward and social-emotional processing systems specifically during social stimuli, including increased functional connectivity of the amygdala with the ventromedial PFC, the orbitofrontal cortex and the precuneus. Similarly, Korisky et al [ 73 ] found that OXT increased neural activity in the frontal regions of the brain in response to social stimuli, as well as in the left hemisphere regardless of the stimulus. Takiguchi et al [ 77 ] discovered that OXT administration enhanced activation in the right middle frontal gyrus and striatum, consistent with enhancements in the mesolimbic dopaminergic reward system.…”
Section: Resultsmentioning
confidence: 87%
“…Damen et al [ 42 ] administered doses ranging from 16–40 IU daily and provided higher doses to participants with larger body surface areas. Gordon et al [ 1 ] and Korisky et al [ 73 ] stratified dosages based on the ages of their participants, while Dadds et al [ 25 ] provided 24 IU daily to participants weighing more than 40 kg and 12 IU daily to participants weighing under 40 kg. Miller et al [ 43 ] provided all participants with 16 IU daily.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations